Understanding parental hurdles in accessing strabismus treatment - Omna Chawla; Anupam Singh; Himani Pal; Sanjeev Kumar Mittal; Srishti Sharma; Mittali Khurana; Pooja Kumari; Barun Kumar (Advances in Ophthalmology Practice and Research)
Purpose: To explore the parental factors that impede early intervention for strabismus and thus identify strategies for improving access to specialized care. Methods: This hospital-based cross-sectional study included 110 parents of children under 19 years with strabismus receiving treatment at the squint clinic of a tertiary health care center in north India. A pre-validated survey questionnaire was administered to the participants, that had a section about the socio-demographics of the participants, another section addressed the parental knowledge about strabismus about diagnosis, and the need for an eye examination. It also sought information about referral source, the felt need for squint examination, and reasons for not seeking treatment. Results: A total of 110 parents/guardians of strabismus patients (59 exotropes and 51 esotropes) were interviewed using a survey questionnaire. Parents themselves identified 80% of cases, and a substantial link (P ​< ​0.0001) was found between the education status of parents and the age of identification of strabismus. Fear of surgical outcomes (41.79%) was a significant barrier to timely surgery with a higher percentage of parents expressing fear of surgical outcomes (P ​= ​0.025). The cost of surgery (34.33%) and the non-availability of facilities (23.88%) also delayed the intervention. Conclusions: It is essential to educate parents about the importance of strabismus therapy at an appropriate time, stressing its reconstructive rather than merely cosmetic nature, as there are notable gaps in their knowledge. Also, we need to do away with the fear of surgical outcomes of surgical interventions for strabismus.